Online Learning Evaluation of Islamic Education Using Context, Input, Process, Product Model - Rifadlin Amin; Dewi Ratna Bian; Nuruh Fathina F. Hamid; Nurasma Ila Ismail; Nurfitri Salamah; Samlan Ahmad; Abdurahman Hi Usman (International Journal of Multidisciplinary Research of Higher Education, 2026)
The digital transformation in higher education has driven a paradigm shift from conventional learning models to the integration of information technology, including Islamic Education courses. This study aims to evaluate the implementation of online learning in Islamic Education at universities by applying Stufflebeam’s evaluation model of Context, Input, Process, and Product. A mixed-methods approach was employed, involving lecturers and students as research participants. Data were collected through questionnaires, in-depth interviews, observations, and document analysis. The findings indicate that online learning in Islamic Education is considered effective in terms of context and input, yet faces significant challenges in process and product. Student participation levels are relatively high but remain suboptimal, with major obstacles including technological access gaps, diverse digital competencies among lecturers, and the reduction of affective values in learning. Cognitive learning outcomes were achieved satisfactorily, while affective and psychomotor domains showed declining quality compared to face-to-face learning. The study recommends strengthening lecturers’ digital literacy, developing blended learning models, and reformulating evaluation systems capable of measuring competencies holistically. These findings contribute to the development of adaptive and meaningful Islamic Education policies in the digital era.